Neighborhood stressors and psychological distress among U.S. Latinos: Measuring the protective effects of social support from family and friends. (7th December 2018) - Bostean, Georgiana; Andrade, Flavia Cristina Drumond; Viruell‐Fuentes, Edna A.
Abstract: We examined whether social support from family and friends, separately, reduce the deleterious effect of neighborhood stressors on psychological distress among Latinos by subgroup. Utilizing data from a nationally representative sample of 2, 524 Latinos (National Latino and Asian American Survey), we found that neighborhood stressors were associated with higher distress among people with low and average levels of family support, although there was no significant association between neighborhood stressors and distress among those with high levels of family support. Although both family and friend support reduced the deleterious mental health impact of neighborhood stressors, when mutually adjusted, only family support remained statistically significant as a stress buffer and only for Mexicans and Cubans.